A chemical genetic screen with the EXO70 inhibitor Endosidin2 uncovers potential modulators of exocytosis in Arabidopsis - Xiaohui Li; Diwen Wang; Xianglin Yin; Mingji Dai; Christopher J. Staiger; Chunhua Zhang (Plant Direct)
Abstract Exocytosis plays an essential role in delivering proteins, lipids, and cell wall polysaccharides to the plasma membrane and extracellular spaces. Accurate secretion through exocytosis is key to normal plant development as well as responses to biotic and abiotic stresses. During exocytosis, an octameric protein complex named the exocyst facilitates the tethering of secretory vesicles to the plasma membrane. Despite some understanding of molecular and cellular aspects of exocyst function obtained through reverse genetics and direct interaction assays, knowledge about upstream modulators and genetic interactors remains limited. Traditional genetic screens encounter practical issues in exocyst subunit mutant backgrounds, such as lethality of certain knockout mutants and/or potential redundancy of EXO70 homologs. To address these challenges, this study leverages the tunable and reversible nature of chemical genetics, employing Endosidin2 (ES2)—a synthetic inhibitor of EXO70—for a large‐scale chemical genetic mutant screen in Arabidopsis. This approach led to the identification of 70 ES2‐hypersensitive mutants, named es2s. Through a whole‐genome sequencing‐based mapping strategy, 14 nonallelic es2s mutants were mapped and the candidate mutations reported here. In addition, T‐DNA insertion lines were tested as alternative alleles to identify causal mutations. We found that T‐DNA insertion alleles for DCP5, VAS1/ISS1, ArgJ, and MEF11 were hypersensitive to ES2 for root growth inhibition. This research not only offers new genetic resources for systematically identifying molecular players interacting with the exocyst in Arabidopsis but also enhances understanding of the regulation of exocytosis.